Investigative Outcomes of CODIS Matches in Previously Untested Sexual Assault Kits - Davis, Robert C. (Criminal justice policy review, 2021)
A 2011 Texas statute required that police agencies submit to the state all unanalyzed sexual assault kits between 1996 and 2011. Cases where a match was made with DNA from an individual or case were returned to local agencies for additional investigation. This article examines outcomes of these cases. Consistent with other studies, we found that the ratio of arrests to all kits submitted was below 1%, and the ratio of arrests to Combined DNA Index System (CODIS) hits was 5.5%. A cost analysis concluded that the cost per court filing was US$132,000. We argue that the small number of arrests was partially due to the age of the cases, based on 8- to 23-year-old crime reports. We further contend that the program could have produced better results if the state had provided funding more quickly for testing and investigations.